Modulatory role of nitric oxide in wound healing of potato tubers - Dogramaci, Munevver; Sarkar, Dipayan; Lulai, Edward C. (Frontiers in Horticulture, 2024)
Wounding of potato (Solanum tuberosum L.) tubers affects the postharvest storage qualities and marketability. To mitigate wound-related losses, it is necessary to accelerate wound healing (WH) responses of potato tubers. While role of nitric oxide (NO) in healing of wounded biological tissues is well known, its impact on WH responses of potato tubers has not been examined thoroughly. The aim of this study was to elucidate the potential modulatory role of NO in WH response of potato tubers by determining the activity of key enzymes associated with NO biosynthesis. Using a model wounding system, tuber tissue discs were extracted from mini tubers of cv. Russet Burbank to examine their WH responses. Tuber discs were treated with NO related chemicals, such as NO scavenger, nitric oxide synthase (NOS) inhibitor, and NO donors. The effect of these treatments on in vitro production of NO, activity of nitrate reductase, NOS, and phenylalanine ammonia-lyase were determined. The accumulation of suberin polyphenolics (SPP) in wounded parenchyma cells, an indicator of early suberization process, was analyzed histologically. Treatment of tuber tissues with the higher dose of an NO scavenger (2-phenyl-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide) at the time of wounding completely ceased SPP accumulation between 0 h to 3 d after wounding. Increased production of NO and enhanced activity of NOS were also observed immediately after wounding of the tuber tissues. The results suggest that NO is a key biological modulator in WH responses of potato tubers and could be optimized as a potential exogenous treatment to counter wound-related losses.